Lamp Light Exposure During Sleep and Sleep Quality of Medical Student Universitas Airlangga Batch 2012 - Dyah Ayu Pradnyaparamitha; Hendrian Dwikoloso Soebagjo; Gadis Meinar Sari (AKSONA, 2022)
Introduction: Sleep disorder commonly happens to teenagers and adults because of light exposure during sleep that affects sleep quality, but the relation of lamp light exposure during sleep and sleep quality of medical students hasn’t been determined previously. Objective: This research aimed to determine the relation of lamp light exposure and sleep quality of Universitas Airlangga’s medical students and to give further information about the right adjustment of lamp light exposure to improve the sleep quality of medical student. Methods: Variables in this cross-sectional designed research were lamp light exposure (on or off) as the independent variable and sleep quality as a dependent variable. The research used the PSQI questionnaire to decide the sleep quality of 115 subjects once a week in a month. The collected data were analyzed by chi-square and fisher’s exact test. Results: Based on the chi-square test, the p-value for lamp light exposure and sleep quality was more than 0.05 (p = 0.863). The results also showed that 74.8%  of medical students had bad quality sleep. Conclusion : In conclusion, there was no relation between lamp light exposure and sleep quality. This research also indicated that most of the subjects had a bad sleep quality so that student should increase their needs for better sleep quality to maintain performance.